Modelo para predição de indicadores de continuidade em um sistema de distribuição de energia elétrica, uma aplicação à gestão de manutenção com a perspectiva do uso da termografia - Araújo Junior, José Arnóbio de (2016)
The Electrical power distribution system (SDEE) of most of the Northeast region concessionaires are old and present different kinds of problems. In an indirect way, these problems can be verified through the collective indicators of continuity, provided by the National Electric Energy Agency (ANEEL). These indicators include the Interruption Equivalent Duration per Consumer Unit (DEC) and the Interruption Equivalent Frequency per Consumer Unit (FEC). In order to improve these indicators, this study proposes a methodology to be applied in the analysis of the history of occurrences (interruptions in power supply) registered in an electricity distribution concessionaire, from January 2013 to December 2014. The methodology proposed here is based on the construction of a model that establishes the DEC and FEC indicators. Once the proposed model is constructed, considering the period of operation of the SDEE to be analyzed, we intend to set the values of DEC and FEC, according to the observed and recorded occurrences for this system. The prior knowledge of DEC and FEC indicators allows the maintenance management, making it possible to measure the influence of the main failure modes on the composition of these indicators. As a basis for the elaboration of the analysis methodology and that of the model, we carried out a research, together with an energy distribution concessionaire, which will be denominated, in this work, as concessionaire A. This research involves a survey of the occurrences of failures (with interruption) within a group of consumers. Data was collected monthly, from January 2013 to December 2014. From these data, a model structure based on Multiple Linear Regression Analysis (ARLM) was constructed. There is, on the part of concessionaire A, the intention to develop maintenance actions that apply thermographic techniques. These techniques allow the thermal gradient mapping of a given energized device, distinguishing different temperatures by means of infrared radiation. For this purpose, the concessionaire A has invested on equipment and personnel training. This study proposes the application of the model which was built, based on ARLM, as a support tool to evaluate the influence of failure modes on the composition of continuity indicators (DEC and FEC). The failure modes of greatest interest are those that are likely to be detected by thermography. The prior knowledge of the influence of failure modes on the composition of these indicators will enable a decision making, aiming at the execution of maintenance actions, allowing the concessionaire to perform a direct action on the feeder and on the most influential modes of failure, especially on those that can be detected by thermography.